Revisiting Indonesian public reactions against Danish cartoons depicting prophet Muhammad - Al Makin (IAIN Salatiga, 2015)
This paper revisits the case of cartoon controversy in 2006, particularly focus-ing on the way in which the Indonesian public reacted against the twelveMuhammad Danish cartoons by the Jylands-Posten published in September 30,2005. The study remains relevant as the case reflects not only Muslims’ reac-tion against the blasphemy theologically but it also mirrors the new face ofIndonesian Islam in the reform era which has given birth to a new free public space in which new differing ideologies emerged and were propagated in various media. This study particularly focuses on the selected thirteen op-ed piecesand one interview published by the Indonesian online media in January 2006—three pieces published by Hidayatullah, one posted in a personal website, twopublished by Kompas, two by The Jakarta Post, one by Gatra, three by Tempoone op-ed and one interview by JIL (Islamic Liberal Network). My analysis ofthese works reveals two groups with different arguments: radical and conservative return to their theological foundation to retaliate the cartoonists whocommitted blasphemy against their prophet, whereas liberals and progressiveIndonesians rely on reasoning and draw cultural values in expressing theirappraisals of the vilifying images.Makalah ini berusaha mengkaji kembali kasus kontroversi kartun pada tahun2006, terutama berfokus pada cara di mana masyarakat Indonesia bereaksiterhadap dua belas kartun Muhammad yang diterbitkan oleh surat kabar Den-mark Jylands-Posten pada tanggal 30 September 2005. Studi ini tetap relevansebagai kasus yang mencerminkan tidak hanya reaksi umat Islam terhadappenghujatan secara teologis tetapi juga mencerminkan wajah baru Islam Indo-nesia di era reformasi yang telah melahirkan ruang publik bebas baru di manaberbagai ideologi baru muncul dan disebarkan di berbagai media. Penelitianini terutama fokus pada tiga belas buah edisi opini dan satu wawancara yangditerbitkan oleh media online Indonesia pada Januari 2006, yang terdiri daritiga potong yang diterbitkan oleh Hidayatullah, yang diposting di sebuah si-tus pribadi, dua diterbitkan oleh Kompas, dua oleh The Jakarta Post, satuoleh Gatra, tiga Tempo, satu op-ed dan satu wawancara dengan JIL (JaringanIslam Liberal). Analisis atas karya-karya ini mengungkapkan dua kelompokdengan argumen yang berbeda: kelompok radikal dan konservatif berpedomanpada landasan teologis mereka untuk membalas kartunis yang melakukanpenghujatan terhadap nabi mereka, sedangkan kaum liberal dan progresif In-donesia mengandalkan penalaran dan menarik nilai-nilai budaya dalammengekspresikan penilaian mereka atas gambar-gambar tersebut.